Management and mechanisms of severe eosinophilic asthma - Shrimanker, R (2020)
Severe asthma is a complex problem in which eosinophilic asthma is an over-represented phenotype compared to mild and moderate asthma. Asthma attacks, for which persistent eosinophilic inflammation is a major risk factor, are the most clinically concerning aspect of this disease as they result in high healthcare use and spending, treatment related morbidity due to oral corticosteroids, and reduced quality of life for patients.